E-019 Clinical, Angiographic, and Radiographic Outcomes Differences Amongst Mechanical Thrombectomy Devices: Initial Experience of a Large-Volume Centre. (14th July 2013) - Kass-Hout, T; Kass-Hout, O; Sun, C; Gupta, R; Nogueira, R
Abstract : Background and purpose: Early Reperfusion is critical for favourable outcome in patients with acute ischaemic stroke (AIS). There are limited data on the comparative performance of FDA approved devices for mechanical thrombectomy. Here, we compare the angiographic, radiographic, and clinical outcomes amongst the three device categories currently available in the U.S. when used in routine clinical practice. Methods: Retrospective review of a prospective collected database of endovascularly treated large vessel AIS in a large academic centre. Data from all consecutive patients who underwent clot retrieval using Merci, Penumbra, or Stent-Retrievers from September 2010 to July 2012 were analysed. Baseline characteristics including age, gender, NIHSS, ASPECTS score, and co-morbidities were compared across the 3 groups. The outcome measures included the rates of recanalisation (TICI 2b-3), symptomatic intracebral haemorrhage (sICH, defined as any parenchymal haematoma e.g. PH-1/PH-2), final infarct volume, 90-day mortality, and independent functional outcomes (modified Rankin Scale, mRS 0–2) at 90 days. Results: The entire cohort included 287 patients with a mean age of 65.5 ± 14.2 and median baseline NIHSS 20. Of the patients 49.38% were females. The median ASPECTS score was 8. There were no significant differences in terms of baseline characteristics amongst the 3 device groups. There were not statistically differences in the rate of sICH (7% vs 7% vs 6%, for Stent retrieval, Merci and Penumbra respectively, P-value = 0.921), and the volume of infarction (66.9, 69.5, and 59.8 cc for Stent retrieval, Merci and Penumbra respectively, P-value = 0.621). However, the rates of TICI 2b-3 reperfusion (86 % vs 70% vs 78 %, p=: 0.027) were significantly higher with Stent-Retrievers and Penumbra system as compared to Merci treatments. This effect remained significant when controlling, for time of stroke onset, ASPECTS score, infarction volume, and co-morbidities. There was no significant difference in the 90-day functional independence (33 % vs 25 % vs 41%, p=0.079) amongst the different devices (for Stent-Retriever, Merci, and Penumbra groups, respectively). Conclusion: Our initial data confirms the superiority of the Stent-Retriever technology over the Merci device in achieving higher rates of reperfusion and better outcomes. No significant difference in near complete/complete reperfusion, final infarct volumes, or clinical outcomes could be established between Stent-Retrievers and Penumbra thromboaspiration. This supports the need for a randomised clinical trial comparing these two technologies. Disclosures: T. Kass-Hout: None. O. Kass-Hout: None. C. Sun: None. R. Gupta: None. R. Nogueira: None.